Informaç\~ao, delegaç\~ao e processo legislativo: A política das medidas provisórias - Acir Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– This study analyses the political correlates of the use of provisionary decrees (medidas provisórias) by Brazilian presidents in law-making. It is argued that the intense use of this legislative tool reflects a tacit delegation of agenda powers from the Congress to the Executive branch, and that such delegation follows an informational logic, in the sense that it is motivated by the interest of congress members in reducing their decision-making uncertainty and limited by the credibility of the Executive's recommendation. Based on this logic, it is expected that decrees will be used more frequently for policies that are less complex, that some parliamentary majority considers urgent to vote on, or for which there is little disagreement between some majority and the Executive. These expectations are backed by correlational evidence from a multivariate analysis that uses original data on law initiatives issued by the Executive between 1989 and 2012.
Keywords: D72; 330; decree; agenda power; delegation; informational theory